Streptomyces sp metabolite(s) promotes Bax mediated intrinsic apoptosis and autophagy involving inhibition of mTOR pathway in cervical cancer cell lines - Dan, Vipin Mohan; Muralikrishnan, Balaji; Sanawar, Rahul; Vinodh, J. S.; Burkul, Bhushan Bapusaheb; Srinivas, Kalanghad Puthankalam; Lekshmi, Asha; Pradeep, N. S.; Dastager, Syed G.; Santhakumari, B.; Santhoshkumar, Thankayyan R.; Kumar, R. Ajay; et al. (Scientific Reports, 2018)
In cervical cancer, the association between HPV infection and dysregulation of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTOR pathway) places mTOR as an attractive therapeutic target. The failure of current treatment modalities in advanced stages of this cancer and drawbacks of already available mTOR inhibitors demand for novel drug candidates. In the present study we identified the presence of a mTOR inhibitor in an active fraction of the ethyl acetate extract of Streptomyces sp OA293. The metabolites(s) in the active fraction completely inhibited mTORC1 and thereby suppressed activation of both of its downstream targets, 4E-BP1 and P70S6k, in cervical cancer cells. In addition, it also stalled Akt activation via inhibition of mTORC2. The mechanism of mTOR inhibition detailed in our study overcomes significant drawbacks of well known mTOR inhibitors such as rapamycin and rapalogs. The active fraction induced autophagy and Bax mediated apoptosis suggesting that mTOR inhibition resulted in programmed cell death of cancer cells. The molecular weight determination of the components in active fraction confirmed the absence of any previously known natural mTOR inhibitor. This is the first report of complete mTOR complex inhibition by a product derived from microbial source.

Molecular networking and whole-genome analysis aid discovery of an angucycline that inactivates mTORC1/C2 and induces programmed cell death - Dan, Vipin Mohan; Vinodh, J. S.; Sandesh, C. J.; Sanawar, Rahul; Lekshmi, Asha; Kumar, R. Ajay; Kumar, T. R. Santhosh; Marelli, Uday Kiran; Dastager, Syed G.; Pillai, M. Radhakrishna (ACS Chemical Biology, 2020)
Rediscovery of known compounds and time consumed in identification, especially high molecular weight compounds with complex structure, have let down interest in drug discovery. In this study, whole-genome analysis of microbe and Global Natural Products Social (GNPS) molecular networking helped in initial understanding of possible compounds produced by the microbe. Genome data revealed 10 biosythethic gene clusters that encode for secondary metabolites with anticancer potential. NMR analysis of the pure compound revealed the presence of a four-ringed benz[a]anthracene, thus confirming angucycline; molecular networking further confirmed production of this class of compounds. The type II polyketide synthase gene identified in the microbial genome was matched with the urdamycin duster by BLAST analysis. This information led to ease in identification of urdamycin E and a novel natural derivative, urdamycin V, purified from Streptomyces sp. OA293. Urdamycin E (Urd E) induced apoptosis and autophagy in cancer cell lines. Urd E exerted anticancer action through inactivation of the mTOR complex by preventing phosphorylation at Ser 2448 and Ser 2481 of mTORC1 and mTORC2, respectively. Significant reduction in phosphorylation of the major downstream regulators of both mTORC1 (p70s6k and 4e-bp1) and mTORC2 (Akt) were observed, thus further confirming complete inhibition of the mTOR pathway. Urd E presents itself as a novel mTOR inhibitor that employs a novel mechanism in mTOR pathway inhibition.